Hierarchical unimodal processing within the primary somatosensory cortex during a bimodal detection task - Parra, Sergio; Díaz, Héctor; Zainos, Antonio; Alvarez, Manuel; Zizumbo, Jerónimo; Rivera-Yoshida, Natsuko; Pujalte, Sebastián; Bayones, Lucas; Romo, Ranulfo; Rossi-Pool, Román (Proceedings of the National Academy of Sciences - PNAS, 2022)
Do sensory cortices process more than one sensory modality? To answer these questions, scientists have generated a wide variety of studies at distinct space-time scales in different animal models, and often shown contradictory conclusions. Some conclude that this process occurs in early sensory cortices, but others that this occurs in areas central to sensory cortices. Here, we sought to determine whether sensory neurons process and encode physical stimulus properties of different modalities (tactile and acoustic). For this, we designed a bimodal detection task where the senses of touch and hearing compete from trial to trial. Two Rhesus monkeys performed this novel task, while neural activity was recorded in areas 3b and 1 of the primary somatosensory cortex (S1). We analyzed neurons’ coding properties and variability, organizing them by their receptive field’s position relative to the stimulation zone. Our results indicate that neurons of areas 3b and 1 are unimodal, encoding only the tactile modality in both the firing rate and variability. Moreover, we found that neurons in area 3b carried more information about the periodic stimulus structure than those in area 1, possessed lower response and coding latencies, and had a lower intrinsic time scale. In sum, these differences reveal a hidden processing-based hierarchy. Finally, using a powerful nonlinear dimensionality reduction algorithm, we show that the activity from areas 3b and 1 can be separated, establishing a clear division in the functionality of these two subareas of S1.